2024
DOI: 10.1021/acschemneuro.3c00603
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Brain and Blood Lipidome Changes following Single and Repetitive Mild Traumatic Brain Injury in Rats

Alexis N. Pulliam,
Eric C. Gier,
David A. Gaul
et al.

Abstract: Traumatic brain injury (TBI) is a major health concern in the United States and globally, contributing to disability and long-term neurological problems. Lipid dysregulation after TBI is underexplored, and a better understanding of lipid turnover and degradation could point to novel biomarker candidates and therapeutic targets. Here, we investigated overlapping lipidome changes in the brain and blood using a data-driven discovery approach to understand lipid alterations in the brain and serum compartments acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…There were 609 tentatively annotated lipids in the dataset at an MSI level 2 [ 43 ] ( Figure 5 ). The isotopic features were summed [ 22 ] and resulting features were divided into subclasses. These included lipids from the carnitine (Car) and free fatty acids (FFAs) subclasses (fatty acid class), diacylglycerols (DG), phosphatic acid (PA), phosphatidylglycerols (PG), and triacylglycerols (TG) subclasses (glycerolipid class), cardiolipin (CL), lysophosphatidylcholine (LPC), lysophosphatidylethanolamine (LPE), phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylinositol (PI), and phosphatidylserine (PS) (phospholipid class), and ceramides (Cer), hexosylceramides (HexCer), sulfoglycolipids (SGL), sphingomyelins (SM), and sphingoid bases (sphingolipid class) ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 609 tentatively annotated lipids in the dataset at an MSI level 2 [ 43 ] ( Figure 5 ). The isotopic features were summed [ 22 ] and resulting features were divided into subclasses. These included lipids from the carnitine (Car) and free fatty acids (FFAs) subclasses (fatty acid class), diacylglycerols (DG), phosphatic acid (PA), phosphatidylglycerols (PG), and triacylglycerols (TG) subclasses (glycerolipid class), cardiolipin (CL), lysophosphatidylcholine (LPC), lysophosphatidylethanolamine (LPE), phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylinositol (PI), and phosphatidylserine (PS) (phospholipid class), and ceramides (Cer), hexosylceramides (HexCer), sulfoglycolipids (SGL), sphingomyelins (SM), and sphingoid bases (sphingolipid class) ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…Samples were randomized and analyzed over a range of 150–2000 m/z . Detailed UPLC-MS methods were previously described [ 22 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that VPA-evoked metabolic changes are complex-positive and negative depending on the source and context-and contribute in part to its effects on the brain. We have recently shown that abnormal behavior following TBI in mice is associated with long-lasting alterations of brain lipids, mainly low phosphatidylethanolamines and high triglycerides [31], while others showed lipidome changes within 24 h after TBI in rats [32,33]. In addition, clinical studies found differential phospholipid profiles in cerebrospinal fluid during the acute phase of TBI between surviving and deceased patients [34], and recently, a large human study revealed an inverse correlation between plasma levels of LPCs and TBI severity, suggesting that LPCs in this context provided protective effects or were a marker for favorable metabolic changes [35].…”
Section: Introductionmentioning
confidence: 99%